Wildfire effects on host-parasite interactions in freshwater streams - Svatos, Emma C., author; Preston, Daniel, advisor; Hart, Sarah, committee member; Wells, Caitlin, committee member (Colorado State University. Libraries, 2024)
Wildfires are increasing in intensity and frequency globally, accentuating the need to understand the implications of fire on community interactions. While previous research has focused on fire effects on free-living species, our knowledge of how wildfires influence parasite interactions with hosts and predators remains limited, especially in freshwater ecosystems. This thesis addresses this knowledge gap and presents results from two distinct multi-year observational field studies that explore how wildfires influence interactions among parasites, hosts, and predators in freshwater streams. In Chapter 1, I used a Before-After-Control-Impact design to compare freshwater snail (Juga plicifera) host populations and trematode parasite communities in Oregon streams before and after wildfire disturbance. In Chapter 2, I investigated host-parasite-predator interactions involving mermithid nematode parasites (Family Mermithidae), mayfly hosts (Order Ephemeroptera), and trout predators (Salvelinus fontinalis, Salmo trutta, and Oncorhynchus clarkia) in the southern Rocky Mountains after severe wildfires. Despite substantial changes to stream habitat, snail host populations and trematode infection patterns and community structure remained relatively stable following fire disturbance in Oregon streams; however, I observed subtle taxon-specific responses to fire, suggesting changes in abundance or behavior of definitive hosts. In Rocky Mountain watersheds, mermithid parasite patterns varied considerably over time in burned streams, which coincided with similar responses in mayfly host densities, suggesting that wildfire indirectly affected mermithid infection patterns through host-density changes in the stream. Host attributes also influenced parasite interactions, as intermediate-size Baetidae mayflies experienced the highest probability of infection. Furthermore, infection prevalences of mayflies consumed by trout were positively related to mayflies in the benthos; yet, infection prevalences in trout stomachs were lower on average, potentially due to parasite-induced behavioral changes in infected mayfly hosts that reduced susceptibility to predation. Wildfire did not seem to affect rates of this predator-parasite interaction, as instances of concomitant predation remained consistent in burned streams over time. Comparing two different host-parasite systems sheds light on how environmental variables and host-parasite ecologies mediate wildfire effects on parasite interactions with hosts and predators. Together these findings expand our knowledge of parasite ecology in aquatic macroinvertebrate hosts, offer insights into the role of parasites in energy flow through food webs and as bioindicators of environmental change, and help integrate parasite interactions into our understanding of disturbance ecology in freshwater streams.
Keywords: disturbance; Mermithidae; wildfire; host-parasite interactions; aquatic ecology; trematode